2023
DOI: 10.1002/adfm.202212997
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Helical Screws of 2D Materials with Archimedean Spiral Arrangement

Abstract: Helix structures, which are frequently observed in nature, act as versatile structural templates for complex functionalities with asymmetry and anisotropy. However, atomically thin 2D materials, including graphene, transition metal dichalcogenides (TMDs), and MXenes, do not have inherent chirality in their planar geometry and cannot easily form such a structure. This study presents the macroscopic self-assembly of 2D materials for helical screws with an Archimedean spiral arrangement. The naturally triggered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Our research group demonstrated a polar solvent-driven graphene fiber actuator (Figure 8d). [205] Due to the spontaneously organized helical screw-like fiber structure achieved through the hierarchical self-assembly of nematic GO liquid crystals, mechanical actuation in the longitudinal direction can be induced under various solvent vapors, including toluene, isopropyl alcohol, ethanol, and acetone. Different polarities and evaporation rates of the solvents yielded different behaviors in the reversible actuation of twisted GO fiber.…”
Section: Solvent-responsive Actuatormentioning
confidence: 99%
See 3 more Smart Citations
“…Our research group demonstrated a polar solvent-driven graphene fiber actuator (Figure 8d). [205] Due to the spontaneously organized helical screw-like fiber structure achieved through the hierarchical self-assembly of nematic GO liquid crystals, mechanical actuation in the longitudinal direction can be induced under various solvent vapors, including toluene, isopropyl alcohol, ethanol, and acetone. Different polarities and evaporation rates of the solvents yielded different behaviors in the reversible actuation of twisted GO fiber.…”
Section: Solvent-responsive Actuatormentioning
confidence: 99%
“…Solvent-based actuators that generate macroscopic mechanical deformation in response to moisture and organic solvents, can be greatly benefited by the incorporation of 2D materials, such as GO, rGO and MXene. [198,205,246] 2D materials with abundant polar functional groups, such as carboxyl and hydroxyl groups, can facilitate a solvent responsiveness by trapping the solvent in their interlayers, leading to the volumetric expansion-based actuation. For instance, an asymmetrical rGO/polypyrrole film has been reported to bend up to 330°while relative humidity increased to 65% with long-term durability over 600 s. [197] Similarly, nacrelike lamellar structure of polydopamine-modified Ti 3 C 2 T x MX-ene/bacterial cellulose nanofiber undergoes the asymmetric water concentration gradient across the film thickness direction in a humid condition, leading to the expansion mismatch and reversible bending of the film.…”
Section: Solvent-responsive Actuatormentioning
confidence: 99%
See 2 more Smart Citations
“…These excellent properties have attracted researchers to mimic nature. Large amounts of artificial helical structures have been exploited by the self-assembled formation based on special DOI: 10.1002/adfm.202305244 geometric features combined with thermal or stress fields during fabrication, including spinning, [3] electrospinning, [4] and biomaterial template manufacturing. [5] With sophisticated structure of helix, various applications have been realized in wide fields such as stimulus-response actuators, [6] remote sensors, [7] helical microrobotics or micromachines, [8] damage resistant composites, [9] 3D crack regulation, [10] etc.…”
Section: Introductionmentioning
confidence: 99%